Transcriptional activation and subsequent control of the human heat shock gene during adenovirus infection. - Kao, H T (1983)
A cDNA copy of the major human heat shock mRNA was cloned. The clone is complementary to the mRNA encoding the major 70-kilodalton heat shock protein as shown by hybrid arrest translation. We utilized the cloned DNA to measure induction of the gene during adenovirus infection. The mRNA increases in abundance approximately 100-fold during a wild-type adenovirus infection but does not increase more than 2-fold during an infection in which there is no E1A gene function [high multiplicity of infection of an E1A (-) mutant]. Furthermore, by measuring transcription in isolated nuclei, we found that the induction was transcriptional and was mediated by the E1A gene product. The induction was not maintained, however. After a peak level was obtained, transcription returned to preinfection levels. This decline was also reflected in the cytoplasmic mRNA abundance indicating a rapid turnover of the heat shock mRNA. This rapid turnover of the heat shock mRNA appears to be induced by the viral infection since the heat shock mRNA was found to be stable when synthesized in an adenovirus-transformed cell line.